Productive urban landscapes: the relationship between urban agriculture and property values in Minneapolis, Minnesota. - Davey, Calayde A. (Kansas State University, 2015)
Urban agriculture and urban food-systems are locally productive landscapes and their supporting programs and networks. Urban agriculture is now valued and actively promoted by many urban communities. Having numerous community benefits, UA is often considered to have desirable neighborhood amenities and is assumed to have effects on nearby property prices. However, very little is known about the primary or secondary economic contribution of these productive landscapes to urban environments, particularly in regards to how urban agriculture relates to property values in a neighborhood. Because urban agriculture sites are often overpowered by increasing exchange-values of surrounding properties, the original values (economic and non-economic) to the neighborhood or community may be lost as urban agricultural sites are transformed by “higher return” development schemes. Since urban agriculture can disappear or fail without effective financing and adequate policy and planning support, it is imperative to the longevity of such programs to understand how important land-use and economic variables interrelate. This study examines the spatial-temporal magnitude and economic relationship between urban agriculture parcels and property values. The study uses the hedonic method employing the Spatial-Durbin modeling approach. Findings expand the theoretical and policy discourse on how investment of public resources aids neighborhood development through low exchange-value programs such as urban agriculture. In understanding the advantages of local food systems to urban form, context-specific neighborhood strategies developed in tandem with targeted community development and comprehensive plans can improve urban revitalization and (re)development within a larger resilient city planning framework. The key findings from the study illustrate that there is great value in understanding the most appropriate design approach and features of urban agriculture for different neighborhoods and market groups. Important design considerations include scale, design aesthetic, abundance and quality of urban agriculture sites within different market groups and neighborhoods.
Keywords: Environmental design; Urban agriculture; Productive urban landscapes; Spatial econometrics; Comprehensive planning; Urban development; Environmental economics (0438); Land Use Planning (0536); Urban Planning (0999)